2017
DOI: 10.1128/aem.01571-17
|View full text |Cite
|
Sign up to set email alerts
|

Akinetes May Be Representative of Past Nostocalean Blooms: a Case Study of Their Benthic Spatiotemporal Distribution and Potential for Germination in a Eutrophic Lake

Abstract: Monitoring of water and surface sediment in a French eutrophic lake (Lake Aydat) was carried out over a 2-year period in order to determine whether akinetes in sediment could be representative of the most recent bloom and to estimate their germination potential. Sediment analysis revealed two akinete species, and, present in the same proportions as observed for the pelagic populations. Moreover, similar spatial patterns observed for vegetative cells in the water column and akinete distributions in the sediment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
19
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 20 publications
(23 citation statements)
references
References 54 publications
2
19
0
2
Order By: Relevance
“…In the uppermost 30 cm, D. macropsorum akinetes were characterized by a low integrity whereas a high one was measured for D. flos-aquae . The same applies in the surface sediment of Lake Aydat, where the percentage of intact akinetes varied from 7 to 60% for D. macroporum and D. flos-aquae respectively [ 27 ]. This high species-dependent variability may be explained by a species-specific sensitivity to ecological factors both in the water column and in sediment [ 21 , 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…In the uppermost 30 cm, D. macropsorum akinetes were characterized by a low integrity whereas a high one was measured for D. flos-aquae . The same applies in the surface sediment of Lake Aydat, where the percentage of intact akinetes varied from 7 to 60% for D. macroporum and D. flos-aquae respectively [ 27 ]. This high species-dependent variability may be explained by a species-specific sensitivity to ecological factors both in the water column and in sediment [ 21 , 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…Under unfavorable conditions, selected toxin producers can form dormant cells known as akinetes, and deposit them in sediments. Whether these akinetes contain cyanotoxins has not been subject to investigation; but it was demonstrated that in some cases, up to several thousands of intact akinetes per g of sediment can be deposited [43]. If these cells contain selected toxins of interest, they would highly contribute to the sedimentary cyanotoxin pool.…”
Section: Determination Of Cyanotoxins In Sediment Coresmentioning
confidence: 99%
“…Very few studies have attempted to reconstruct MC production prior to recent human development around lake systems (pre-150 years); most studies have utilized a variety of extraction techniques, and one of two analytical techniques: liquid chromatography-mass spectrometry (LC-MS), or gas chromatography-mass spectrometry (GC-MS) ( Tables 1 and 2). Recently, a longer history of potential MC production was constructed from akinetes, and by sequencing genes related to MC synthesis isolated from a sediment core from Lake Aydat, France [43]. While records of historic MC production are slowly being produced and timelines are being extended, a comprehensive extraction technique and a detailed understanding of MC degradation and transformation post-deposition have yet to be established.…”
Section: Microcystins (Mcs)mentioning
confidence: 99%
See 2 more Smart Citations